Is upregulation of BCL2 a determinant of tumor development driven by inactivation of CDH1/E-cadherin? - Inga Karch; Elisa Schipper; Henriette Christgen; Hans Kreipe; Ulrich Lehmann; Matthias Christgen (PLoS ONE, 2013)
Inactivation of CDH1, encoding E-cadherin, promotes cancer initiation and progression. According to a newly proposed molecular mechanism, loss of E-cadherin triggers an upregulation of the anti-apoptotic oncoprotein BCL2. Conversely, reconstitution of E-cadherin counteracts overexpression of BCL2. This reciprocal regulation is thought to be critical for early tumor development. We determined the relevance of this new concept in human infiltrating lobular breast cancer (ILBC), the prime tumor entity associated with CDH1 inactivation. BCL2 expression was examined in human ILBC cell lines (IPH-926, MDA-MB-134, SUM-44) harboring deleterious CDH1 mutations. To test for an intact regulatory axis between E-cadherin and BCL2, wild-type E-cadherin was reconstituted in ILBC cells by ectopic expression. Moreover, BCL2 and E-cadherin were evaluated in primary invasive breast cancers and in synchronous lobular carcinomas in situ (LCIS). MDA-MB-134 and IPH-926 showed little or no BCL2 expression, while SUM-44 ILBC cells were BCL2-positive. Reconstitution of E-cadherin failed to impact on BCL2 expression in all cell lines tested. Primary ILBCs were almost uniformly E-cadherin-negative (97%) and were frequently BCL2-negative (46%). When compared with an appropriate control group, ILBCs showed a trend towards an increased frequency of BCL2-negative cases (P = 0.064). In terminal duct-lobular units affected by LCIS, the E-cadherin-negative neoplastic component showed a similar or a reduced BCL2-immunoreactivity, when compared with the adjacent epithelium. In conclusion, upregulation of BCL2 is not involved in lobular breast carcinogenesis and is unlikely to represent an important determinant of tumor development driven by CDH1 inactivation.